2023
DOI: 10.3892/ol.2023.13917
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA PTCSC3 suppresses triple‑negative breast cancer by downregulating long non‑coding RNA MIR100HG

Abstract: Long non-coding RNA (lncRNA) PTCSC3 is characterized as a tumor suppressor in thyroid cancer and glioma. The present study aimed to investigate the role of PTCSC3 in triple-negative breast cancer (TNBC). A total of 82 patients with TNBC were enrolled in the present study. The results showed that PTCSC3 was downregulated, while lncRNA MIR100HG was upregulated in tumor tissues compared with that in adjacent non-cancerous tissues of patients with TNBC. The follow-up study showed that low expression levels of PTCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The analysis revealed that the lncRNA MIR100HG was significantly overexpressed in TNBC but not in other cancer types. Furthermore, elevated levels of lncRNA MIR100HG in TNBC patients were correlated with a poor prognosis [ 19 , 20 ]. At the post-transcriptional level, lncRNAs can regulate gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis revealed that the lncRNA MIR100HG was significantly overexpressed in TNBC but not in other cancer types. Furthermore, elevated levels of lncRNA MIR100HG in TNBC patients were correlated with a poor prognosis [ 19 , 20 ]. At the post-transcriptional level, lncRNAs can regulate gene expression.…”
Section: Introductionmentioning
confidence: 99%